Minimal Yet Powerful: The Role of Archaeal Small Heat Shock Proteins in Maintaining Protein Homeostasis - Roy, Mousam; Bhakta, Koustav; Ghosh, Abhrajyoti (Frontiers in Molecular Biosciences, 2022)
Small heat shock proteins (sHsp) are a ubiquitous group of ATP-independent chaperones found in all three domains of life. Although sHsps in bacteria and eukaryotes have been studied extensively, little information was available on their archaeal homologs until recently. Interestingly, archaeal heat shock machinery is strikingly simplified, offering a minimal repertoire of heat shock proteins to mitigate heat stress. sHsps play a crucial role in preventing protein aggregation and holding unfolded protein substrates in a folding-competent form. Besides protein aggregation protection, archaeal sHsps have been shown recently to stabilize membranes and contribute to transferring captured substrate proteins to chaperonin for refolding. Furthermore, recent studies on archaeal sHsps have shown that environment-induced oligomeric plasticity plays a crucial role in maintaining their functional form. Despite being prokaryotes, the archaeal heat shock protein repository shares several features with its highly sophisticated eukaryotic counterpart. The minimal nature of the archaeal heat shock protein repository offers ample scope to explore the function and regulation of heat shock protein(s) to shed light on their evolution. Moreover, similar structural dynamics of archaeal and human sHsps have made the former an excellent system to study different chaperonopathies since archaeal sHsps are more stable under in vitro experiments.